Răspuns :
235) (1-a)(1-b)(1-c) ≥ 8abc
Înlocuim 1 = a+b+c și membrul stâng al relației devine:
(a+b+c-a)(a+b+c-b)(a+b+c-c) = (b+c)(a+c)(a+b) ≥ 2√(bc)·2√(ac)·2√(ab)=
= 8√(a²b²c²) = 8abc.
233)
m, n, k∈N
Avem inegalitățile evidente :
mn ≤ mnk
mk ≤ mnk
nk ≤ mnk
Prin adunare, obținem :
mn + mk + nk ≤ 3mnk
229)
(a + b)⁴ = [(a + b)²]² = (a² + 2ab + b²)² = [(a²+b²) +2ab]² ≥(a² + b²)² =
= a⁴ + b⁴ +2a²b² ≥ a⁴ + b⁴
Înlocuim 1 = a+b+c și membrul stâng al relației devine:
(a+b+c-a)(a+b+c-b)(a+b+c-c) = (b+c)(a+c)(a+b) ≥ 2√(bc)·2√(ac)·2√(ab)=
= 8√(a²b²c²) = 8abc.
233)
m, n, k∈N
Avem inegalitățile evidente :
mn ≤ mnk
mk ≤ mnk
nk ≤ mnk
Prin adunare, obținem :
mn + mk + nk ≤ 3mnk
229)
(a + b)⁴ = [(a + b)²]² = (a² + 2ab + b²)² = [(a²+b²) +2ab]² ≥(a² + b²)² =
= a⁴ + b⁴ +2a²b² ≥ a⁴ + b⁴